Synthesis, characterization, and photocatalytic activity of N-doped carbonaceous material derived from cellulose in textile dye remediation. Issue 3 (June 2017) - Chhetri, Bijay P.; Soni, Dave; RanguMagar, Ambar Bahandur; Parnell, Charlette M.; Wayland, Hunter; Watanabe, Fumiya; Kannarpady, Ganesh; Biris, Alexandru S.; Ghosh, Anindya
Graphical abstract: Highlights: N-doped carbonaceous material of microcrystalline cellulose and urea was prepared. The material was used in textile dye remediation via photocatalytic oxidation. The material was highly efficient towards dye degradation under visible light. The cellulose-derived material was recycled for multiple uses in dye remediation. The mechanism of degradation and role of oxygen and radical quenchers are proposed. Abstract: N-doped carbonaceous materials were synthesized by pyrolysis of microcrystalline cellulose and urea at 900 °C. The pyrolyzed materials were characterized via SEM, XPS, STEM/EDX, and FT/IR. Microscopy images revealed wrinkled sheet-like morphology with stacked graphitic layers, and elemental analyses confirmed 7.74% nitrogen content, which was evenly distributed throughout the material. The characteristic peaks of CN and CN bonds in FT/IR indicated N-atom incorporation in the material. The catalytic experiment with alcian blue 8Gx dye under visible light showed higher degradation than in dark, which illustrated the photocatalytic nature of the material. The pH conditions and material ratios were optimized during the photocatalytic experiments. Various dyes were subjected to degradation photocatalytically using the materials at pH 5.5 and recyclability studies indicated multi-cycle use of the material. Additionally, kinetic studies of the photocatalytic degradation of indigo carmine showed that the disappearance of the dye followed a first-order kinetics. The significance of adsorption phenomena in the process of degradation was established by comparing the adsorption constant (KLH = 0.898 L mg −1 ) calculated using the Langmuir-Hinshelwood model with that calculated based on the adsorption isotherm model (KL = 0.2457 L mg −1 ). Degradation products were characterized via various analytical techniques, including GC–MS, ion chromatography, FT/IR, and total organic carbon analyses. Furthermore, the role of oxygen and radical quenchers were studied and it was found that the main species responsible for dye degradation was hydroxyl radical. N-doping of cellulose via a simple pyrolysis method has therefore been proven to be effective in development of photocatalytic materials for pollutant mitigation.